Influence of Preinfarction Angina on the Long-Term Survival Rate of Non-Thrombolized Patients - Miranda Rivas, Gustavo (1999)
OBJECTIVES: To evaluate the influence of preinfarction angina on the long-term survival rate of non-thrombolized patients. MATERIAL AND METHODS: A prospective, observational study, in which 122 patients admitted at the coronary care unit at Hospital Nacional Edgardo Rebagliati Martins with a diagnosis of acute myocardial infarction (AMI) who did not undergo thrombolysis and survived to the acute intrahospitalary period, who were followed through a period of 5 years, was made. The main outcome measures were overall mortality and cardiac events. Patients were divided into 4 groups according to the presence or not, and characteristics of preinfarction angina. RESULTS: Kaplan-Meier analysis showed that those with preinfarction angina had a shorter survival and more cardiac events, as compared with those without preinfarction angina (p < 0,05). History of angina more than 30 days before AMI also correlates with shorter survival and more cardiac events, as compared with those without preinfarction angina or with recent onset angina (p <0,05). CONCLUSIONS: Non-thrombolized patients with history of previous angina had a worst long-term prognosis, with the exception of those with early onset angina.